2021
DOI: 10.1021/acs.energyfuels.0c04081
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Slickwater Effect on Permeability of Gas Shale from Longmaxi Formation

Abstract: Knowing of gas shale permeability reduction is vital for gas production from shale gas reservoirs stimulated by multistage hydraulic fracturing. However, the role of shale matrix permeability reduction is not well addressed for evaluating the contribution on gas well production. In this study, the experiments of slickwater treatment at different injection pressures, injection volumes, and slickwater compositions were conducted by using an experimental apparatus based on the steady-state method. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In addition to the initiation sequence, perforation cluster spacing and well spacing, the properties of the rock mass and fracturing fluid also control the stress shadow effects. Physical constraints such as subsurface temperatures, pressure and geological formation fluid complexity may also affect the performance of chemical additives and hydraulic fracturing fluids (Liu et al, 2021;Harry et al, 2020;Reynolds, 2020).…”
Section: Controlling Factors Of Stress Shadowsmentioning
confidence: 99%
“…In addition to the initiation sequence, perforation cluster spacing and well spacing, the properties of the rock mass and fracturing fluid also control the stress shadow effects. Physical constraints such as subsurface temperatures, pressure and geological formation fluid complexity may also affect the performance of chemical additives and hydraulic fracturing fluids (Liu et al, 2021;Harry et al, 2020;Reynolds, 2020).…”
Section: Controlling Factors Of Stress Shadowsmentioning
confidence: 99%
“…The second review by Zhang and Cheng is a mini review on the technical aspects of sample preparation and data analysis using small-angle neutron scattering (SANS) and ultrasmall-angle neutron scattering (USANS) for shale samples. The original research articles cover a wide spectrum of research on shale gas, including reservoir characteristics, ,,, reservoir modeling, ,,, exploration, equipment-related, ,, gas transport properties, ,,,, shale property characterization, , gas adsorption, ,, gas generation, produced water treatment, , methane conversion, etc.…”
Section: Shale Gasmentioning
confidence: 99%
“…In situ viscosity reduction of heavy oil water thermal cracking fundamentally solves the problem of the high viscosity of heavy oil, so it has created wide interest among researchers, among which the core of hydrothermal cracking technology is the catalyst. The oil-soluble catalyst can fully contact with the oil phase, which can better improve the efficiency of catalyzing the heavy oil water thermal cracking reaction and reduce the viscosity of heavy oil [10,11]. Zhao et al [12] successfully reduced the viscosity of Liaohe heavy oil by more than 90% using nickel-and cobalt-based catalysts and petroleum sulfonates as emulsifiers at a lower reaction temperature of 180 • C. Chao et al [13] used a 0.2% copper aromatic sulfonate composite catalyst to heat asphalt heavy oil at 280 • C for 24 h, and found that the viscosity of heavy oil decreased by 95.5%.…”
Section: Introductionmentioning
confidence: 99%